“We’re on a Merry-Go-Round”: Reflections of Patients and Carers after Completing Treatment for Sarcoma - Weaver, Rhys; O’Connor, M.; Carey Smith, R.; Sheppard, D.; Halkett, Georgia (MDPI, 2021)
Sarcoma is a rare cancer that has a significant impact on patients’ and carers’ quality of life. Despite this, there has been a paucity of research exploring the diverse experiences of patients and carers following sarcoma treatment. The aim of this study was to explore patients’ and carers’ reflections on life after treatment for sarcoma. A qualitative research design with a social constructionist epistemology was used. Participants included patients previously treated for sarcoma (n = 21) and family carers of patients treated for sarcoma (n = 16). Participants completed semi-structured interviews which were analysed using thematic analysis. Three primary themes were identified: “This journey is never going to be over”, “But what happens when I am better?”, and finding a silver lining. Participants represented sarcoma as having a long-term, and sometimes indefinite, threat on their life that they had limited control over. Conclusions: This study highlight the heterogeneous and ongoing needs of sarcoma survivors and their families. Patients and carers strove to translate their experiences in a meaningful way, such as by improving outcomes for other people affected by sarcoma. Parental carers in particular attempted to protect the patient from the ongoing stress of managing the disease.